Personality Dynamics and Theoretic Procedures in Sigmund Freud’s Psychoanalytic Counseling: A Literature Review - Kamalia, Nur Kistin; Purwoko, Budi; All Habsy, Bakhrudin (Jurnal Indonesia Sosial Sains, 2026)
The psychoanalytic theory developed by Sigmund Freud provides a fundamental foundation for understanding the structure of personality and human psychosexual development. This article aims to analyze, in depth, the basic concepts of psychoanalysis, the mechanisms of ego defense, as well as their clinical application in the counseling process. The method used is a literature review, comparing various reference sources related to the implementation of psychoanalysis. The results of the study show that the success of counseling is highly dependent on the ego’s ability to balance conflicts between the id and the superego through specific techniques such as free association and transference analysis. The findings also suggest that psychoanalysis remains relevant in contemporary counseling due to its capacity to explore the depth of personality and the symbolic meaning of behavior. The implications of this study are that counselors need to integrate an understanding of unconscious dynamics with appropriate therapeutic techniques to enhance the effectiveness of interventions, particularly in cases involving trauma and long-standing psychological conflict. The conclusions of this study confirm that, although it is a classical theory, psychoanalysis remains relevant for examining the roots of psychological problems stemming from past experiences.